The effects of the global financial crisis on brazilian banking efficiency - Wolters, Mark Edward (2022)
With Brazil and the BRIC economies becoming more important to world growth and financial investment, it is important to understand the inner-workings of the financial institutions that will help spur on continued economic growth. This article focuses on the recent history of the market structure of the Brazilian banking sector as well as the effects of the global financial crisis of the late 2000s on the overall relative efficiency of the Brazilian banking sector by using Data Envelopment Analysis. The period studied—2002-2011—shows a marked decrease in overall relative efficiency in the Brazilian banking sector. The negative effects were felt across the board regardless of bank size or ownership type. Small and medium sized banks had the most significant drop in relative efficiency while larger banks were able to weather the crisis more successfully. This alludes to the idea that “Bigger is Better” when dealing with financial shocks to banking efficiency, and would allow us to summarize that the Brazilian banking sector is not participating in the “Quiet Life” of concentrated markets. Also, looking at ownership type, the study shows that Brazilian banks that are controlled by the government were ranked as the most efficient types of banks. Their foreignowned counterparts, however, were ranked as the least efficient and had a larger drop in overall efficiency and participation during the financial crisis than their domestic Brazilian counterparts. The article contributes to the continued need for more information on the Brazilian banking sector’s history and development.